Book Review: American Indian/First Nations Schooling: From the Colonial Period to the Present - Eryka Charley (Journal of Research in Rural Education, 2013)
From the Colonial Period to the Present is Charles L. Glenn's analysis of the schooling of the North American Indian through an educational policy and administration perspective. While the title implies a chronological outline of Indian education, each chapter title presents a particular subject within Indian education, while the chapter explores the historical background with regard to the subject.